STUDI ANALISIS KURIKULUM ILMU FALAK UIN ALAUDDIN MAKASSAR BERBASIS INTEGRASI ASTRONOMI - Primantyas, Bagus Herdianto; Wakia, Nurul; HR, Sabriadi (HISABUNA: Jurnal Ilmu Falak, 2026)
ABSTRACT This re$se$arch focuse$s on analyzing the$ curriculum$ of phalac scie$nce$ at the$ State$ Islam$ic Unive$rsity of Alauddin M$akassar base$d on astronom$y inte$gration. The$ form$ulation of this proble$m$ include$s: how is the$ curriculum$ of phalac scie$nce$ at Alauddin M$akassar State$ Islam$ic Unive$rsity, how is the$ astronom$ical inte$gration of the$ curriculum$ of phalac scie$nce$ at Alauddin M$akassar State$ Islam$ic Unive$rsity. This re$se$arch use$s a library re$se$arch m$e$thod by analyzing the$ astronom$y inte$gration-base$d astrophysics curriculum$ through source$s obtaine$d from$ books, article$s, the$se$s, and re$ports on pre$vious re$se$arch re$sults that are$ re$le$vant to this re$se$arch. The$ re$sults of this study are$ the$ re$alistic le$arning of astrophysics applie$d by the$ Falak Scie$nce$ Study Program$ at Alauddin M$akassar State$ Islam$ic Unive$rsity has 63 course$s with 147 cre$dits consisting of 13 Unive$rsity com$pulsory course$s, 22 Faculty course$s and 26 Falak Scie$nce$ Study Program$ course$s. Of the$ 26 course$s in the$ Falak Scie$nce$ Study Program$ that ne$e$d to be$ adde$d are$ 13 course$s, nam$e$ly Lunar E$clipse$ Hisab, Solar E$clipse$ Hisab, Non-Optic Rukyat De$vice$s, Optical Rukyat De$vice$s, Advance$d Falak Scie$nce$ Te$xt Studie$s, Hisab and Rukyat Practice$s, Basics of Astronom$y, Basics of Sphe$rical Astronom$y, Basics of Physics, M$athe$m$atics. Hisab Rukyat Study of Diffe$re$nt Countrie$s, Astronom$y and Culture$, Calculator Algorithm$s and Program$m$ing, Com$pute$r Algorithm$s and Program$m$ing (E$xce$l), Com$pute$r Algorithm$s and Program$m$ing (VB and Android), and Statistics. The$ im$plication of this re$se$arch is that the$ Falak Scie$nce$ Study Program$ is e$xpe$cte$d to re$duce$ le$gal course$s to fit the$ focus of the$ acade$m$ic fie$ld and re$vie$w or re$vie$w the$ e$xisting curriculum$ at othe$r unive$rsitie$s.